Self‐report pain and symptom measures for primary dysmenorrhoea: A critical review. (March 2015) - Chen, C.X.; Kwekkeboom, K.L.; Ward, S.E.
Abstract: Primary dysmenorrhoea (PD) is highly prevalent among women of reproductive age and it can have significant short‐ and long‐term consequences for both women and society as a whole. Validated symptom measures are fundamental for researchers to understand women's symptom experience of PD and to test symptom interventions. The objective of this paper was to critically review the content and psychometric properties of self‐report tools to measure symptoms of PD. Databases including PubMed, PsychoINFO, Cumulative Index of Nursing and Allied Health Literature, and Health and Psychosocial Instruments were searched for self‐report symptom measures that had been used among women with either PD or perimenstrual symptoms. A total of 15 measures met inclusion criteria and were included in the final analysis. The measures were categorized into generic pain measures, dysmenorrhoea‐specific measures, and tools designed to measure perimenstrual symptoms. These measures had varying degrees of comprehensiveness of symptoms being measured, relevance to PD, multidimensionality and psychometric soundness. No single measure was found to be optimal for use, but some dysmenorrhoea‐specific measures could be recommended if revised and further tested. Key issues in symptom measurement for PD are discussed. Future research needs to strengthen dysmenorrhoea‐specific symptom measures by including a comprehensive list of symptoms based on the pathogenesis of PD, exploring relevant symptom dimensions beyond symptom severity (e.g., frequency, duration, symptom distress), and testing psychometric properties of the adapted tools using sound methodology and diverse samples.